The Texas collaborative center for hepatocellular cancer: Reducing liver cancer mortality in Texas through coordination, collaboration and advocacy - Harrison, Ariel C.; Kanwal, Fasiha; Asrani, Sumeet K.; Thrift, Aaron P.; Amos, Chris I.; Jibaja-Weiss, Maria L.; Montealegre, Jane R.; Hwang, Jessica P.; Singal, Amit G.; El-Serag, Hashem B. (Frontiers in Oncology, 2022)
Texas has the highest age-adjusted incidence rate of hepatocellular carcinoma (HCC) in the United States. To address cancer prevention and early detection through research, Cancer Prevention and Research Institute of Texas (CPRIT) has funded the Texas Collaborative Center for Hepatocellular Cancer (TeCH) to facilitate liver cancer research, education and advocacy activities. This paper describes the organizational structure, program measures, the actions completed and future plans of TeCH. This center is comprised of several cores and committees including the Administrative Core, Steering Committee, Data and Biospecimen Core, Scientific Committee, Clinical Network Committee, and the Community Outreach Committee. Each core and committee provide its own level of connectivity and necessary research support. We have developed and published a TeCH Framework, a conceptual model designed for improving primary and secondary prevention of HCC. TeCH and its committees facilitate connections and collaborations among HCC researchers and clinicians, healthcare leaders, biotechnology companies and the public to reduce liver cancer mortality in Texas by 2030.